2013
DOI: 10.1098/rspb.2013.2175
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence that extra-pair mating drives asymmetrical introgression of a sexual trait

Abstract: Theory suggests that traits under positive selection may introgress asymmetrically across a hybrid zone, potentially driven by sexual selection. Two subspecies of the red-backed fairy-wren (Malurus melanocephalus) differ primarily in a sexual signal used in mate choice-red versus orange male back plumage colour-but phylogeographic analyses suggest asymmetrical introgression of red plumage into the genetic background of the orange subspecies. We hypothesized that this asymmetrical introgression may be facilitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
64
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 49 publications
3
64
0
Order By: Relevance
“…Five SNP clines had centers located east of the plumage cline, supporting the idea that eastward genetic introgression in some parts of the genome could have been substantial enough to recombine “red alleles” from the cruentatus subspecies into the genomic background of the orange melanocephalus subspecies. Previous work has shown that experimentally reddened males in an allopatric population of the melanocephalus subspecies sire significantly more extra‐pair offspring than orange males (Baldassarre and Webster ). The greater reproductive success of red males may provide the selective force driving the observed introgression, eroding one potential barrier between the subspecies.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Five SNP clines had centers located east of the plumage cline, supporting the idea that eastward genetic introgression in some parts of the genome could have been substantial enough to recombine “red alleles” from the cruentatus subspecies into the genomic background of the orange melanocephalus subspecies. Previous work has shown that experimentally reddened males in an allopatric population of the melanocephalus subspecies sire significantly more extra‐pair offspring than orange males (Baldassarre and Webster ). The greater reproductive success of red males may provide the selective force driving the observed introgression, eroding one potential barrier between the subspecies.…”
Section: Discussionmentioning
confidence: 98%
“…TetraColorSpace produces several values that quantify the hue, saturation, and brightness of a color. For this study, we focused on one measure of hue, theta ( θ ), because previous analyses have shown that it best captures the variation in red to orange that characterizes the subspecies (Baldassarre et al ; Baldassarre and Webster ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, hybridization between Red-backed Fairy-wren (Malurus melanocephalus cruentatus) and Orange-backed Fairy-wren (Malurus m. melanocephalus) across the Carpentarian Barrier in Australia has led to the introgression of red plumage colour into the Orange-backed subspecies (Figure 4.1B, Baldassarre et al, 2014). An experimental study showed that artificially reddened males have significantly more extra-pair offspring compared to orange males, which suggests that greater reproductive success of red males drives the observed introgression (Baldassarre and Webster, 2013). A similar situation has been described in Panama, where yellow plumage colour of Golden-collared Manakin (Manacus vitellinus) has spread into the populations of the White-collared Manakin (Manacus candei) by means of strong sexual selection at mixed leks, where males of both species gather to attract mates , Parsons et al, 1993, Stein and Uy, 2006.…”
Section: Natural and Sexual Selectionmentioning
confidence: 99%